ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI KEPUTUSAN MAHASISWA MEMILIH PROGRAM PASCASARJANA - mahmudah, mahmudah; muhammad Baga, Lukman; amanah, Siti (TADBIR MUWAHHID, 2019)
The study aimed to determine factors influence the decision making the process of the students to choose master or doctorate programs at the at Department of Resources and Environmental Economics, FEM IPB. This research was conducted by using the quantitatively descriptive analysis and multiple regression analysis methods. A survey to 54 the students of Magister and a survey to 51 the students of Doctor was administered to learn the reason of the students took the final decision to the further study at the at Department of Resources and Environmental Economics, FEM IPB. The variables observed were the product, price, location, promotion, process, people, physical evidence, assignments from workplace institutions, availability of sponsors, self-motivation. The data collection technique used was the distribution of questionnaires, namely using the google form that was disseminated through student e-mail, social media and direct distribution to students. Based on the results of the research the decision making process of graduate students to choose the graduate programs are through five steps. Based on the research results of the factors that have a significant effect on the decision of students to choose the Postgraduate Program at the at Department of Resources and Environmental Economics, FEM IPB are products (Study Program), promotion and self-motivation (students).